Comparison of the wear behavior of WC/(FeAl-B) and WC-Co composites at high temperatures. (September 2017) - Mottaghi, M.; Ahmadian, M.
Abstract: In this research, the sliding wear behavior of the hot pressed WC/40 vol%(FeAl-B) composites was investigated at temperatures ranging from the ambient one to those as high as 600 °C. The composites were then compared with hot pressed WC-40 vol%Co and commercial WC-16 vol%Co (H10F) in terms of their mechanical properties and high temperature wear behavior. It was found that the WC/(FeAl-B) composite recorded its maximum wear resistance at all the experimental temperatures, which was higher than that of WC-40 vol%Co at these same temperatures due to the higher hardness of the FeAl-B than that of the Co matrix. Also, WC/(FeAl-B) exhibited a higher wear resistance at lower temperatures and a more proper behavior at higher temperatures than did the commercial WC-16 vol%Co; this was attributed to the higher strength of the FeAl-B matrix at high temperatures. Examination of the wear surfaces revealed that abrasion was the wear mechanism in the commercial WC-16 vol%Co and WC/(FeAl-B) composites at both ambient temperature and 300 °C. At 400 °C, however, the wear mechanism was more of an adhesive one, while binder oxidation was observed at 600 °C. Highlights: WC-40 vol%(FeAl-B) composite exhibited higher hardness and fracture toughness than that of WC-40 vol%Co cermet. WC-40 vol%(FeAl-B) composites showed higher wear resistance than WC-Co with similar amount of matrix. The wear mechanism of WC/(FeAl-B) was abrasion at ambient temperature and at 300 °C. The wear mechanism of WC/(FeAl-B) changed to adhesion at 400 °C. For WC/(FeAl-B) composite, the oxidation mechanism was the main wear mechanism at 600 °C.